The Discourse of Islam and Other Religions by Early ʻUlamā’ in the Malay World - Abdul Jalil, Mohd Noh (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The article analyses the discourse of early ʻulamā’ in the Malay world such as Nuruddin al-Raniri and Abdul Rauf al-Sinkili on Islam and other religions. Early ʻulamā’ in the Malay world wrote numerous intellectual works for the need of local as well as international audiences. The history of religions in the Malay world revealed interesting facts on the diversity of religions that existed and were practiced by the local people. The question now is on how early ʻulamā’ in the Malay world addressed the presence and influence of religions other than Islam during the early period of Islam in the Malay world. In order to find an answer to this question, this article analyses the topic of interest written by these early ʻulamā’. The analysis is also expanded to the discourse between local ʻulamā’ and their counterparts all over the world. Special focus is given to the discourse on religions other than Islam written by early ʻulamā’ in the Malay world in order to understand their priority at that time. This article concludes that the discourse in the writings of early ʻulamā’ in the Malay world corresponds with their counterparts worldwide. The main discourse is still on the fundamental teachings of Islam. Nevertheless, discourse on religions other than Islam was not totally neglected. The limited discourse on religions other than Islam in the works of early ʻulamā’ in the Malay world implicitly tells us about the priority of early ʻulamā’ in the Malay world at that time in propagating the messages of Islam to the local people.